Is there an app for that? A cluster randomised controlled trial of a mobile app–based mental health intervention. (September 2020) - Kenny, Rachel; Fitzgerald, Amanda; Segurado, Ricardo; Dooley, Barbara
Demand for the use of mobile apps in mental health interventions has grown in recent years, particularly among adolescents who experience elevated levels of distress. However, there is a scarcity of evidence for the effectiveness of these tools within this population. The aim of this study was to test the effectiveness of CopeSmart, a mental health mobile app, using a multicentre cluster randomised controlled trial design. Participants were 15–18-years-olds (N = 560) recruited from 10 schools randomly assigned to an intervention or control condition. Intervention participants used the app over a 4-week period. Multi-level modelling analyses revealed no significant changes in the intervention group from pre-test to post-test, when compared to the control group, in terms of emotional distress, well-being, emotional self-awareness or coping strategies. Findings suggest that a 4-week app-based intervention may not be enough to elicit intra-personal changes in mental health outcomes in a general adolescent population.